Pengaruh Kemiringan Lereng dan Penggunaan Lahan terhadap beberapa Sifat Fisika Tanah di Sub-DAS Cikapundung Hulu - Abraham Suriadikusumah; Ridha Hudaya; Adhe Sigit Sutanto (Soilrens, 2014)
This research was conducted to find out the effect of various slope classes and land use types on porosity, permeability and soil's aggregate stability index. The research was carried out from June up to December 2009 in Upper Cikapundung Sub Watershed which area was located in West Bandung Regency and Subang Regency, West Java. The method used in this research was explorative survey method. Sampling technique which used based on purposive stratified sampling method. Soil sampling was carried onto three various slope classes in three various land uses, which consist of: 8- 15% slope classes in pine forest, 8-15% slope classes in secondary forest, 8-15% slope classes in tea plantation, 15-30% slope classes in pine forest, 15-30% slope classes in secondary forest, 15-30% slope classes in tea plantation, 30-45% slope classes in pine forest, 30-45% slope classes in secondary forest and 30-45% slope classes in tea plantation. The result of this research showed that highest soil total porosity achieved in 8-15% slope classes in secondary forest, 8-15% slope classes in pine forest, 15-30% slope classes in all land use and 30-45% slope classes in all land use. Highest permeability achieved in 8-15% slope classes in all land use, 15-30% slope classes in tea plantation, 15-30% slope classes in pine forest and 30-45% slope classes in tea plantation. Soil index aggregate stability achieved in 8-30% slope classes in secondary forest, 8-30% slope classes in tea plantation and 30- 45% slope classes in all land use